2011
DOI: 10.1007/s11655-011-0822-z
|View full text |Cite
|
Sign up to set email alerts
|

Yiqi Zhuyu Decoction (益气逐瘀汤) Combined with FOLFOX-4 as first-line therapy in metastatic colorectal cancer

Abstract: YZD combined with FOLFOX-4 chemotherapy significantly improved OS in this first-line trial in the patients with MCRC and significantly decreased grade 3/4 AEs. However, RR was not improved, and PFS did not reach statistical significance by the addition of YZD. The treatment of YZD combined with FOLFOX-4 may be necessary in order to optimize efficacy and safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All studies stated the use of randomization. Fifteen studies (35.7%) described a proper method of sequence generation (SG), so risk of bias was judged as “low.” Two studies 24,25 described allocation concealment (AC), used blinding of participants (BPt) and a placebo control for the TM, so these were judged “low risk” for these domains. The other studies did not describe procedures for AC, so were judged “unclear risk” for AC and “high risk” for BPt since the participants would know they were receiving an additional therapy.…”
Section: Resultsmentioning
confidence: 99%
“…All studies stated the use of randomization. Fifteen studies (35.7%) described a proper method of sequence generation (SG), so risk of bias was judged as “low.” Two studies 24,25 described allocation concealment (AC), used blinding of participants (BPt) and a placebo control for the TM, so these were judged “low risk” for these domains. The other studies did not describe procedures for AC, so were judged “unclear risk” for AC and “high risk” for BPt since the participants would know they were receiving an additional therapy.…”
Section: Resultsmentioning
confidence: 99%
“…(Taiwan) in 2010 (http://www.doh.gov.tw/EN2006/index_EN.aspx/). Recently, various studies have shown that traditional Chinese medicine (TCM) and folklore medicine possessed potential anticolorectal cancer activity and they are associated with a reduced risk of cancer [24]. It has been reported that the TCM and folklore medicine can induce reactive oxygen species (ROS) production and DNA damage, which leads to increased phosphorylation of ataxia-telangiectasia-mutated kinase (ATM) and p53 and then triggers apoptosis in human cancer cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…Following screening, 45 studies were included in the meta-analysis (Figure 1). 7-51 All studies met the requirements of 5-FU regimen combined with TCM intervention versus 5-FU regimen alone. The TRR was provided as well.…”
Section: Resultsmentioning
confidence: 99%